Neo-simple methodology for the evaluation of potential botanical insect repellents and the rapid comparative study on specific chemical and photo sensitivity of selected insects - Aravind Gopal; Benny PJ (International Journal of Life Sciences, 2018)
The study was to evaluate the insect repellent activity of certain plants and to compare the sensitivity of certain insects towards selected essential oils, composite light and a few colors. While on the experimental arena, chemical and photo sensitivity tests were carried out using a ‘modified T-maze’ called as ‘A-B sensitivity apparatus’. Plant parts were extracted using methanol-water and ethyl acetate. Essential oil was extracted with hydro distillation method. Preliminary evaluation procedure was focused on repellent activity against Sitophilus granarius, but further studies used more insect species. Using new indices, the repellent and insect potential were compared. In Preliminary evaluation, 18 out of 19 plants showed repellent activity. Further studies on the essential oil of available plants showed that, Merremia vitifolia has the highest repellent activity than the Peperomia Pellucida and the positive control, Elettaria cardamomum. Merremia vitifolia essential oil have the lowest absolute effective surface concentration and highest repellent index. Considering the Insect properties, Sitophilus granarius is the strongest and hence had the highest Anti-Repellent Index of 5.8421 μl/gcm2 against Elettaria cardamomum essential oil. In photo sensitivity test all the insects showed more affinity towards the middle of the visible spectrum and are repelled by darkness.